Can a UV-C box help cinema industry by hygienizing video-cameras?. (20th October 2021) - Messina, G; Limaj, S; Amodeo, D; De Palma, I; Petri, C; Cevenini, G
Abstract: Background: UV-C has proven to be an effective microbiocide method for disinfecting objects in domestic and work environments. Aim of this study was to test the biocidal efficiency of an UVC box on a real video-camera. Methods: In February 2021, a descriptive study on a parallelepiped-shaped UVC box, produced by Cartoni S.p.a., was conducted at the University of Siena. The box has 10 UV-C lamps (254 nm at 0.9 Watt/each) and all six mirrored reflective walls. It was specifically engineered for disinfecting equipments for film makers. A real professional camera was used to assess the level of disinfection. Contamination was obtained inoculating 1.5x107CFU/mL of S. Aureus ATCC 43300 on five 20 cm2 plastic carriers positioned in five different spots (referred as spots A, B, C, D, E), both directly (spot A), and indirectly (by reflected light, spots B, C, D, E) exposed to a UV-C light source. After a cycle of 3 minutes' exposition to UV-C: all carriers were transferred on empty Petri dishes; 10 mL D/E medium was added, transferred into a 50 ml Falcon and spun for 40 minutes at 4500 rpm; the supernatant was then removed and 100 µl of it was incubated into a Petri dish (with a generic growth medium) at 36 °C for 48 h. The experiment was run in triplicate. The mean logarithmic reduction and its 95% confidence interval were calculated from the replicates data and compared with positive controls (1.5x107CFU/mL). Results: Mean logarithmic reduction compared to positive control was in spot A: 6.33 log10(C.I. 5.90-6.75), spot B: 4.74 log10(C.I. 4.11-5.33), spot C: 4.83 log10(C.I. 4.75-4.91), spot D: 4.89 log10(C.I. 4.12-5.65), spot E: 5.00 log10(C.I. 4.79-5.21). Conclusions: These experiments showed that after 3 minutes of UV-C exposure there is a significant reduction in the bacterial load, 4 to 6 log10 (99.99% to 99.9999% reduction), on the carriers. The results also highlight the ability of the UV-C box to disinfect all infected spots, including those irradiated by reflected light. Key messages: UV-C Box devices are effective in decreasing bacterial contamination on shared work tools in cinema industries, regardless of the direct or indirect exposition to the UV-C source. UV-C box's speed in hygienizing shared work tools can help cinema industry professionals to work in a safer and cleaner environment.